Short-term Responses of Posidonia australis to Changes in Light Quality - Strydom, Simone; McMahon, Kathryn M.; Kendrick, Gary A.; Statton, John; Lavery, Paul S. (Frontiers in Plant Science, 2018)
Seagrass meadows are highly productive ecosystems that provide ecosystem services to the coastal zone but are declining globally, particularly due to anthropogenic activities that reduce the quantity of light reaching seagrasses, such as dredging, river discharge and eutrophication. Light quality (the spectral composition of the light) is also altered by these anthropogenic stressors as the differential attenuation of wavelengths of light is caused by materials within the water column. This study addressed the effect of altered light quality on different life-history stages of the seagrass Posidonia australis, a persistent, habitat-forming species in Australia. Aquarium-based experiments were conducted to determine how adult shoots and seedlings respond to blue (peak λ = 451 nm); green (peak λ = 522 nm); yellow (peak λ = 596 nm) and red (peak λ = 673 nm) wavelengths with a control of full-spectrum light (λ = 400 – 700 nm, at 200 μmol photons m-2 s-1). Posidonia australis adults did not respond to changes in light quality relative to full-spectrum light, demonstrating a capacity to obtain enough photons from a range of wavelengths across the visible spectrum to maintain short-term growth at high irradiances. Posidonia australis seedlings (<4 months old) grown in blue light showed a significant increase in xanthophyll concentrations when compared to plants grown in full-spectrum, demonstrating a pigment acclimation response to blue light. These results differed significantly from negative responses to changes in light quality recently described for Halophila ovalis, a colonizing seagrass species. Persistent seagrasses such as P. australis, appear to be better at tolerating short-term changes in light quality compared to colonizing species when sufficient PPFD is present.